What caused Bashir’s fall in 2019? ---A comparative analysis between Sudan’s protests during the Arab Spring and those starting from 2018 - Chen, Mengran (Université d'Ottawa | University of Ottawa, 2021)
On 11 April, 2019, Sudan’s president Omar Hassan al-Bashir was forced to step down by his own internal-security apparatus after a series of demonstrations since 2018 that demanded urgent economic reforms and the fall of the regime. The former president ruled the country for about three decades and witnessed numerous protests during his tenure. He also faced protests during the Arab Spring but his regime remained intact in that wave of protest. This paper is to explore what has caused al-Bashir’s fall in 2019. By comparing the period of Arab Spring and the period of 2018-2019, this paper put forward two hypothese to try to explain the successful ousting of al-Bashir in 2019. And through the analysis, this paper has found that it is in interaction between political opportunities and structures that we see the shift in the possibility for the successful ouster of al-Bashir.